Synthesis of nanosilver particles mediated by microbial surfactants and its enhancement of crude oil recovery. (1st June 2023) - Liu, Yu-Long; Li, Yang; Si, Yin-Fang; Fu, Jian; Dong, Hao; Sun, Shan-Shan; Zhang, Fan; She, Yue-Hui; Zhang, Zhi-Quan
Abstract: In view of the increasingly high demand for environmental protection in oil fields, new environmentally friendly materials that can replace harmful chemicals must be urgently studied. In this study, the biofriendly reducing agent "ascorbic acid" was selected to prepare nanosilver, and a biological nanosilver composite (Bio-Ag) was synthesized using the fermentation supernatants of Candida and P. aeruginosa, which were refrigerated in the laboratory as modifiers and dispersants. Furthermore, sand-filled pipe and micromodel oil displacement experiments were conducted. XRD results confirmed the formation of nanosilver, and its crystal structure was FCC. SEM results showed that the size of the nanosilver was 15–60 nm, and the shape was irregular ellipsoid, angular, or rod shaped. FT-IR results showed that microbial metabolism produced bioactive substances, such as glycolipids and peptides, which were modified on the surface of the nanoparticles. In the laboratory, displacement experiments of nanosilver dispersed by sodium dodecyl sulfate (SDS-Ag), Candida fermentation supernatant (C–Ag), and Pseudomonas aeruginosa (P–Ag) were conducted, and the oil recovery increased by 13.6%, 19.49%, and 11.4%，respectively. Results of the microdisplacement experiment showed that nanoparticles had strong adsorption capacity in the pore throat and had good stripping effect on residual oil. Graphical abstract: Image 1 Highlights: Bio-nano, environmentally friendly materials are used in enhanced oil recovery. Microbial metabolism produces glycolipids, peptides, and other bioactive substances to modify nanoparticles. Sand-filled pipe and micromodel oil displacement experiments of biological nanofluids.